Decay Mode Solutions for Kadomtsev-Petviashvili Equation - 樊国号 邓淑芳 张孟 (Communications in theoretical physics, 2012)
The decay mode solutions for the Kadomtsev-Petviashvili （KP） equation are derived by Hirota method （direct method）.The decay mode solution is a new set of analytical solutions with Airy function.